Reconstructing the Author for a Wide Audience: Dickens in Doctor Who (2005) and Assassin’s Creed (2015) - Clémence Folléa (Études Britanniques Contemporaines, 2018)
This article belongs to an academic trend of works that study twenty-first-century culture by looking at its representations of the past. More particularly, it seeks to investigate how and why the British cultural heritage can be twisted and transformed in contemporary creations targeting a broad audience. It focuses on two popular productions, an episode from the cult TV series Doctor Who and an instalment in the multimillion-dollar franchise of videogames Assassin’s Creed, which both feature the figure of Dickens. These rely on an apparently mainstream version of the author to build a comfortable representation of the Victorian past, which is thus turned into an easily enjoyable background setting. Nevertheless, the confrontation between such a household reconstruction and the series’/game’s specific aesthetics causes some disruption, suggesting that the British past can also be turned into a cultural playground in which contemporary productions may generate new imaginative experiences.